Azetidines‐Containing Fluorescent Purine Analogs: Synthesis and Photophysical Properties. Issue 30 (12th April 2022) - Hadidi, Kaivin; Tor, Yitzhak
Abstract: Analogues of N, N ‐dimethyladenine exploiting both thieno‐and isothiazolo‐pyrimidine cores were modified with 3‐subsituted azetidines to yield visibly emissive and responsive fluorophores. The emission quantum yields, among the highest seen for purine analogues (0.64 and 0.77 in water and dioxane respectively), correlated with the Hammett inductive constants of the substituents on the azetidine ring. Ribosylation of the difluoroazetidino‐modified nucleobase yielded an emissive nucleoside that displayed a substantially lower emission quantum yield in water, compared to the precursor nucleobase. Importantly, high emission quantum yield was restored in deuterium oxide, which highlights the potential impact of the sugar moiety on the photophysical features of fluorescent nucleosides, a functionality usually considered non‐chromophoric and photophysically benign. Abstract : Analogues of N, N ‐dimethyladenine exploiting both thieno‐and isothiazolo‐pyrimidine cores were modified with 3‐subsituted azetidines to yield visibly emissive and responsive fluorophores. Ribosylation of the difluoroazetidino‐modified nucleobase yielded an emissive nucleoside that displayed a substantially lower emission quantum yield in water, compared to the precursor nucleobase. The impact of the sugar moiety on the photophysical features of fluorescent nucleosides, a functionality usually considered non‐chromophoric and photophysically benign, was analyzed.